Law and the limits of reason - Vermeule, Adrian, 1968- (Oxford : New York ; Oxford University Press, 2009)
Vermeule denies the view that the limits of reason counsel in favour of judges making 'living' constitutional law in the style of the common law. Instead, he proposes and defends a 'codified constitution' - a regime in which legislatures have the primary authority to develop constitutional law over time.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Law -- Methodology; Law -- United States -- Methodology